Manmohanomics : journey to South Block (life of an Indian prime minister) - Garg, Vivek; Mishra, Ravish (New Delhi : Manas Pub, 2004)
On the life and political contribution of Manmohan Singh, b. 1932, Prime Minister of India
Includes index
Keywords: Manmohan Singh -- 1932-; Prime ministers -- India -- Biography; India -- Politics and government -- 1977-